Het failliet van de integratie? : het multiculturalismedebat in Vlaanderen - Van den Broeck, Bob; Foblets, Marie-Claire (Leuven: Acco, 2002)
"Bob Van den Broeck en Marie-Claire Foblets (red.) Bibliotheek Roland Moreels"